Faecal Sludge Management in Urban Environment, Omni Processor an Innovative Technology. Issue 1 (June 2021) - Vyas, Anil D; Swami, Suman
Abstract: Comparing to wastewater management practices, various treatment options available for Faecal Sludge (FS) are almost a century old. 2.7 billion People across the globe, mainly in the developing nations are relying on "On Site Sanitation Systems", OSS or unsewered sanitation. This situation will last for decades as city wide sanitation through sewer lines is neither feasible nor affordable. It is estimated that by the year 2030, almost five billion people across the globe would be relying on OSS. This paper focuses on issues of FS in developing nations, the huge gaps in sanitation value chain, the technological options available and innovations in treating FS through "Omni Processor". With ultimate aim of removing pathogens and converting FS into water and electricity it works on various technological options that are not limited to super critical oxidation, pyrolysis, combustion and so on.